2015
DOI: 10.1590/1516-3180.2014.9182710
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis in pregnant adolescents: proinflammatory cytokine and bacterial sialidase profile. Cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Bacterial vaginosis occurs frequently in pregnancy and increases susceptibility to sexually transmitted infections (STI). Considering that adolescents are disproportionally affected by STI, the aim of this study was to evaluate the cervicovaginal levels of interleukin (IL)-1 beta, IL-6, IL-8 and bacterial sialidase in pregnant adolescents with bacterial vaginosis. DESIGN AND SETTING: Cross-sectional study at mother and child referral units in Belém, Pará, Brazil. METHODS:Vaginal samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
14
0
7
Order By: Relevance
“…In contrast, Marrazzo suggests that there is evidence to support a role for acquisition of BV, but this process may vary among subsets of women [ 57 ]. Elevated cervicovaginal levels of interleukin (IL)-1 beta, IL-6, and IL-8, which are higher in pregnant adolescents with BV, may increase one’s vulnerability to a STI [ 58 ].
Fig.
…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…In contrast, Marrazzo suggests that there is evidence to support a role for acquisition of BV, but this process may vary among subsets of women [ 57 ]. Elevated cervicovaginal levels of interleukin (IL)-1 beta, IL-6, and IL-8, which are higher in pregnant adolescents with BV, may increase one’s vulnerability to a STI [ 58 ].
Fig.
…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…Sanita C, et al (2015) also reported that 35 of the total 52 pregnant patients with bacterial vaginosis were detected in the presence of enzyme activity levels of the enzyme sialidase with a median of 10.3 ng/ml (range 0.0-163.3 ng/ml) were correlated with preterm labour and membranes ruptured. 11 In this study, vaginal sialidase levels in threatened of preterm labour median result of 736.41 pg/ml (73.641 ng/ml). The results of these studies support the conclusion that the bacteria associated with an enzyme that affects the mucosal barrier that can provide entry for bacteria into the reproductive tract that will cause a local infection in the birth canal.…”
Section: Discussionmentioning
confidence: 53%
“…При воспалительных заболеваниях вульвы и влагалища также отмечается повышение синтеза ФНО-альфа и ИЛ-1, в т. ч. и у беременных пациенток [9][10][11]. Повы шенный цитокиновый фон, высокая активность G. vagi nalis на фоне дополнительной супрессии нормальной микрофлоры влагалища антисептиками могут провоцировать быструю гибель нормальных клеток слизистой в зоне воспаления в результате процесса пироптоза [12,13].…”
Section: патогенетическое обоснование применения бензидамина при острunclassified